Tinjauan hukum terhadap praktik pembagian wilayah dagang oleh pedagang sayur keliling di kabupaten Purworejo: Perspektif undang- undang nomor 5 tahun 1999 tentang larangan praktik monopoli dan persaingan usaha tidak sehat - ningsih, tri wahyu (Maliki Interdisciplinary Journal, 2025)
Unfair business competition is often found in various industries. This study examines the practice of dividing trading areas by vegetable vendors in Purworejo Regency from the perspective of Law Number 5 of 1999 concerning the Prohibition of Monopolistic Practices and Unfair Business Competition. Through an empirical legal approach, it was found that the practice of dividing areas that requires new traders to pay a certain amount of money to old traders to obtain the right to sell in a certain area fulfills the elements of an agreement prohibited in Article 9 of Law Number 5 of 1999. This practice has the potential to create local monopolies and hinder fair business competition. Legally, the perpetrators can be subject to administrative sanctions by the KPPU. This study recommends the need for further education and supervision of business actors in the informal sector in order to create a fair and competitive business climate.